Research advances in anammox granular sludge: A review. Issue 5 (4th March 2022) - Adams, Mabruk; Xie, Junxiang; Kabore, Arthur wendinso Judicael; Chang, Yaofeng; Xie, Jiawei; Guo, Menglei; Chen, Chongjun
Abstract: The slow growth rate of the anammox bacteria (AnAOB) resulting in a long startup period of the anammox process has resulted in scientists trying to find a long-lasting solution. Anammox granular sludge (AnGS) application is one such solution being proffered by researchers in order to ensure the feasibility of industrial-scale anammox application. Granulation of anammox sludge, compared to other enrichment strategies used by scientists to help shorten the startup of the anammox process, appears to be the most feasible option for the realization of large-scale anammox application, since it is stated to be effective in the retention of biomass and, unlike the addition of carriers, further ensures an even better mixing of biomass. In this review, the properties, influencing factors, limitations, cultivation, and the detailed research progress of the application of anammox granules are discussed. It is hoped that this review could serve as an invaluable guide in future research and engineering applications of anammox granular sludge (AnGS). Graphical abstract: